Advanced technologies in InGaN micro-LED fabrication to mitigate the sidewall effect - Zhiyuan Liu; Haicheng Cao; Xiao Tang; Tingang Liu; Yi Lu; Zixian Jiang; Na Xiao; Xiaohang Li (Light: Science & Applications, 2025)
Abstract The size of InGaN micro-LEDs is continuously decreasing to meet the demands of various emerging applications, especially in tiny micro-displays such as AR/VR. However, the conventional pixel definition based on plasma etching significantly damages the mesa sidewalls, leading to a severe reduction in efficiency as the micro-LED size decreases. This seriously impedes the development and application of micro-LEDs. In this work, we comprehensively explain the origin of micro-LED sidewall effects and corresponding physical models. Subsequently, we systematically review recent progress in micro-LED fabrication aiming at suppressing sidewall effects. Furthermore, we discuss advancements in micro-LED fabrication with “damage-free” techniques, which hold the potential to fundamentally address the issue of plasma damage in the micro-LED process. We believe this review will deepen the understanding of micro-LED sidewall effects and provide a better insight into the latest associated fabrication technologies for high-efficient InGaN micro-LEDs.